Physicochemical Studies of Ni/Al Layered Double Hydroxide at Ambient Temperature - Mohd Johari, Siti Nurul 'Afini; Deraman, Siti Khatijah; Hanibah, Hussein; Tajuddin, Nazrizawati Ahmad (Asian Journal of Chemistry, 2025)
The Ni/Al layered double hydroxide (Ni/Al LDH) was synthesized via alkali free co-precipitation method with ratio of 4:1. The product of co-precipitation was undergone aging process for 24 h. Then, it was placed in oven at 100 ºC overnight and finally was calcined at 450 ºC for 13 h. The correlation of crystallinity; morphology and particle size of Ni/Al LDH before and after calcination were examined and compared. Thermogravimetric analysis (TGA) was used to evaluate the interlayer anion and carbonate content of Ni/Al LDH. Powder X-ray diffraction (PXRD) was used to study the textural and structural characteristics of the samples. Particle size, morphology and particle properties were characterized by Brunauer-Emmett-Teller (BET) and field emission scanning electron (FESEM). The bonding and structural of Ni/Al LDH was studied by Fourier transform infrared (FTIR).